Illegal Philatelic Issues in the Name of the Republic of Rwanda, Depicting Sri Lankan Snake Images - Indraneil, Das; Anslem, de Silva; Jayantha, Jinasena (International Society for the History and Bibliography of Herpetology, ISHBH, 2016)
The Republic of Rwanda, a landlocked country in east-central Africa, is bordered by Uganda, Burundi, the Democratic Republic of the Congo, and Tanzania. The first philatelic materials known from the country were from German East Africa, until after World War II and conquest by Belgium. Postal usage of stamps indicated as from Ruanda-Urundi were then issued, up to the time of independence in 196.